Study on Estimation of Inhalation and Ingestion Dose due to 222Rn Concentration in Different Types of Ground Water of Some Taluks of Uttara Kannada District, Karnataka, India - Suresh, S.; Srinivasa, E. (Journal of Scientific Research, 2022)
The primary goal of this study was to determine the risk due to radon concentration in drinking water. Water is essential for most of the life on the Earth, and the quality of drinking water is a key criterion for one's health. Radon (222Rn) and radium (226Ra) are the radioactive elements that can be found in water. Thirty samples of drinking water were collected in Haliyal, Joida, and Mundgod taluks of Uttara Kannada district. Emanometry technique was used to determine the concentration of 222Rn activity. The activity concentration of 222Rn in water varies between 3.78 ± 0.38 Bq l-1. and 135.96 ± 1.72 Bq l-1 with a mean value of 26.23 ± 0.65 Bq l-1. The cumulative average annual effective doses for all of the samples under investigation are well below the safe limit of 100 µSv y-1 suggested by WHO.